Photo-Induced Ignition of Different Gaseous Fuels Using Carbon Nanotubes Mixed with Metal Nanoparticles as Ignitor Agents. Issue 6 (3rd June 2017) - Carlucci, A. P.; Visconti, P.; Primiceri, P.; Strafella, L.; Ficarella, A.; Laforgia, D.
ABSTRACT: This article describes the photo-induced ignition process of multi-walled carbon nano-tubes (MWCNTs)/ferrocene mixtures by pulsed Xe lamps using programmable driving boards with adjustable parameters, such as variable flash rate and pulse's energy/intensity. Varying the energy of incident light pulse, minimum ignition energy values were found as a function of mixture weight ratio, observing that a higher MWCNT amount with respect to metal nano-particles leads to lower ignition energy. The photo-induced ignition of CNTs mixed with nano-particles was then used in a properly realized experimental setup for triggering the combustion of CNT-enriched fuel mixtures. Different types of gaseous fuels mixed with air (CH4, liquid propane, and H2 ) were tested. The combustion process triggered by MWCNTs/ferrocene photo-ignition shows better performances, for all used gaseous fuels and for all tested air/fuel ratios, compared with those obtained by using a traditional spark plug. In particular, CNT-based photo-induced combustion evolves more rapidly with shorter ignition delays, higher peak pressure values, and a higher fuel burning rate as observed by reported experimental tests.